PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUASAN KONSUMEN SMARTPHONE ASUS MAHASISWA FAKULTAS EKONOMI PROGRAM STUDI MANAJEMEN UNIVERSITAS SURAKARTA - Argasha, Denis Volindo; Slamet, Giarti (Surakarta Management Journal, 2020)
This study aims to analyze and explain the factors of Product Quality, Price and Promotion that affect the Consumer Satisfaction of Smartphone Asus Students of the Faculty of Economics, Management Study Program, University of Surakarta. This research approach is a quantitative approach, because this research is presented with numbers. The sample in this study were 80 students from the Faculty of Economics, Surakarta University Management Study Program. The analysis model in this study uses multiple linear regression analysis with the help of SPSS VERSION 16.0 for windows.The results of the statistical analysis of this study where the Simple Linear Regression Test has shown: Y = 9.503 - 1,652 X1 + 1,231 X2 + 0.944 X3. T test results obtained: Product Quality (X1) obtained a significant coefficient of 0.001 with the value of t count> value of t table (-3.390> 1.991) thus Product Quality (X1) has a positive effect on Consumer Satisfaction (Y). Price (X2) obtained a significant coefficient of 0,000 with a value of t arithmetic> value of t table (7.258> 1.991) thus Price (X2) had a positive effect on Consumer Satisfaction (Y). Promotion (X3) obtained a significant coefficient of 0.031 with a value of t arithmetic> value of t table (2,200> 1,991) thus Promotion (X3) has a positive effect on Consumer Satisfaction (Y). Based on the F Test obtained an Fcount of 23,329 with a Significant of 0,000. The calculated F value> F table (23,329> 4.01) can thus be concluded that Product Quality (X1), Price (X2) and Promotion Variable (X3) has a positive effect on the Consumer Satisfaction variable (Y).From the calculation results it is known the amount of adjusted Determination Coefficient (R Square) is 0.577. This means that 57.7% of Customer Satisfaction can be explained by three variables of Quality, Price and Promotion, while the remaining 42.3% is influenced by other factors that cannot be explained in this study.